Implementasi Customer Relationship Management dan Dampaknya Terhadap Citra Lembaga pada Yayasan Nurul Hayat Surabaya - Pradany, Adam Adi; Fahrullah (Jurnal Ekonomika dan Bisnis Islam, 2020)
Lembaga Amil Zakat (Amil Zakat Institution) as a non profit oriented organization in their operation should has a good relationship with its contributors. Customer relationship management is needed to maintain a good relationship with its contributors to keep their loyality and have sense of belonging to the institution. This study aims to determine how the implementation of customer relationship management and its impact on nurul hayat foundation. The result of this study indicate that the implementation of customer relationship management has a good impact on the institution. This study used descriptive qualitative method.